2018
DOI: 10.1158/1535-7163.mct-17-1223
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Influence of ROS, pH, and CLIC1 Membrane Protein in the Regulation of G1–S Phase Progression in Human Glioblastoma Stem Cells

Abstract: Glioblastoma (GB) is the most lethal, aggressive, and diffuse brain tumor. The main challenge for successful treatment is targeting the cancer stem cell (CSC) subpopulation responsible for tumor origin, progression, and recurrence. Chloride Intracellular Channel 1 (CLIC1), highly expressed in CSCs, is constitutively present in the plasma membrane where it is associated with chloride ion permeability. , CLIC1 inhibition leads to a significant arrest of GB CSCs in G phase of the cell cycle. Furthermore, CLIC1 kn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…A special attention should be paid to those subgroups containing the M pattern. According with Peretti et al, the fact that CLIC1 membrane expression is crucial for cancer stem cells proliferation it may represent a potential therapeutic target (14). In accordacne with this, cc RCC subgroups with M pattern may be considered of high risk.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A special attention should be paid to those subgroups containing the M pattern. According with Peretti et al, the fact that CLIC1 membrane expression is crucial for cancer stem cells proliferation it may represent a potential therapeutic target (14). In accordacne with this, cc RCC subgroups with M pattern may be considered of high risk.…”
Section: Discussionmentioning
confidence: 97%
“…CLIC1 is characterized by a high versatility regarding its ability to translocate from cytosol to the nucleus and/or the plasma membrane during malignant transformation (12), based on its ability to spontaneously convert from soluble to an integral membrane-bound form. This changeable state is most probably regulated by the membrane lipid composition, especially by cholesterol, together with external factors, such as oxidation and pH (13,14), however, a precise mechanism is currently unknown. Once CLIC1 is incorporated in the plasma membrane, tumor cells become highly active, with a rapid proliferation rate (15), increased invasiveness (16) and metastatic potential (17).…”
mentioning
confidence: 99%
“…The currents correlate with the tumor aggressiveness indicating a positive correlation between membrane form of CLIC1 to glioblastoma, and these results indicate that CLIC1 could be translocated to the membranes in tumor environments. Similar to gastric cancer cells, CLIC1 is shown to regulate ROS accumulation and pH changes in human glioblastoma stem cells influencing their proliferation as well as their motility, and therefore could be a crucial therapeutic target (Gritti et al, 2014;Peretti et al, 2018). CLIC1 was one among the nine genes identified in a screen for ion channels strongly modified in solid tumors and vascular malformations, especially in glioblastoma and bladder cancers (Biasiotta et al, 2016).…”
Section: Clic1mentioning
confidence: 99%
“…CLIC1 plays an active part in this development. According to recent investigations, membrane CLIC1 protein is involved in cellular proliferation, migration and infiltration by increasing cytosol oxidation and pH alkalization [12,14,19]. All these activities are promoted by chloride permeability, which has been associated with the presence of CLIC1 protein in the membrane in several studies.…”
Section: Clic1 Protein Membrane Localization As a Neurodegenerative Mmentioning
confidence: 99%
“…Recent investigation demonstrated that tmCLIC1 and NADPH oxidase are involved in a feed-forward mechanism that increases the production of reactive oxygen species (ROS) [12], particularly in macrophages [13]. This is instrumental in speeding up the transition G1/S phase during the cell cycle [14]. Furthermore, it has been demonstrated that CLIC1 is involved in axonal outgrowth [15], suggesting a functional role of the protein in relation to the cytoskeleton [16,17].…”
Section: Introductionmentioning
confidence: 99%